Different neuroinflammatory profile in amyotrophic lateral sclerosis and frontotemporal dementia is linked to the clinical phase. Issue 1 (17th September 2018) - Oeckl, Patrick; Weydt, Patrick; Steinacker, Petra; Anderl-Straub, Sarah; Nordin, Frida; Volk, Alexander E; Diehl-Schmid, Janine; Andersen, Peter M; Kornhuber, Johannes; Danek, Adrian; Fassbender, Klaus; Fliessbach, Klaus; et al.
Abstract : Objective: To investigate the role of neuroinflammation in asymptomatic and symptomatic amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) mutation carriers. Methods: The neuroinflammatory markers chitotriosidase 1 (CHIT1), YKL-40 and glial fibrillary acidic protein (GFAP) were measured in cerebrospinal fluid (CSF) and blood samples from asymptomatic and symptomatic ALS/FTD mutation carriers, sporadic cases and controls by ELISA. Results: CSF levels of CHIT1, YKL-40 and GFAP were unaffected in asymptomatic mutation carriers (n=16). CHIT1 and YKL-40 were increased in gALS (p<0.001, n=65) whereas GFAP was not affected. Patients with ALS carrying a CHIT1 polymorphism had lower CHIT1 concentrations in CSF (−80%) whereas this polymorphism had no influence on disease severity. In gFTD (n=23), increased YKL-40 and GFAP were observed (p<0.05), whereas CHIT1 was nearly not affected. The same profile as in gALS and gFTD was observed in sALS (n=64/70) and sFTD (n=20/26). CSF and blood concentrations correlated moderately (CHIT1, r=0.51) to weak (YKL-40, r=0.30, GFAP, r=0.39). Blood concentrations of these three markers were not significantly altered in any of the groups except CHIT1 in gALS of the Ulm cohort (p<0.05). Conclusion: Our data indicate that neuroinflammation is linked to the symptomatic phase of ALS/FTD and shows a similar pattern in sporadic and genetic cases. ALS and FTD are characterised by a different neuroinflammatory profile, which might be one driver of the diverse presentations of the ALS/FTD syndrome.